The Effectiveness of Using Wordwall Media on Student Learning Interest IPAS at Madrasah Ibtidaiyah - Muhammad Fadhilah; Gusti Nurmalasari (Journal of Elementary Education Research and Practice, 2025)
IPAS learning at MI Siti Mariam Banjarmasin faces challenges due to students' low interest and limited engagement during lessons. This study aims to evaluate the effectiveness of Wordwall, a gamified instructional medium, in enhancing students' learning interest compared to Educaplay. A quantitative approach was employed using a pretest-posttest control group design with 30 purposively selected students from a population of 46. Data were collected through questionnaires and analyzed using a paired sample t-test via SPSS version 26. Results revealed that the experimental group using Wordwall achieved a "Very High" level of interest (average score 53.36), while the control group using Educaplay reached a "Moderate" level (average score 41.00). A significance value of 0.000 < 0.05 confirmed that Wordwall significantly increases students' interest in learning